Improvement of Social Inclusion-Based Rural Library Management and Services to Support Sustainable Development Goals (SDGs) - Fadhli, Rahmat; Bustari, Meilina; Raharja, Setya; Sugiyono, Sugiyono (International Journal of Public Devotion, 2023)
The rural library is one of the existing facilities in the village and has an integral role as a center for community empowerment activities. In the management of the village library, there are several problems faced, such as many people who do not know the rural library, lack of competence for library managers, non-standard library management, lack of public interest in reading, and low community participation in the rural library program. This service aims to promote social inclusion-based village library programs that can increase community participation and even improve welfare through programs provided to the community. The service was carried out at the Rural Library of Giripurwo Village, Girimulyo District, Kulon Progo Regency, Special Region of Yogyakarta. The target group for community service is the entire rural community, including village officials and village library managers. The results of the service program are that the management of the rural library has become national standard and the programs owned by the village library also accommodate and increase community participation. So that community skills can increase and increase in social inclusion-based rural library programs.